E-071 The utility of vw-mr imaging in the pre-therapeutic work-up of selected patients with complex aneurysms or pseudoaneurysms: illustrative cases. (23rd July 2017) - Deib, G; Wasserman, B; Lim, M; Toth, G; Obusez, E
Abstract : Background and Purpose: There has been growing interest in direct visualization of the vessel wall with high-resolution vessel wall MR imaging (VW-MR imaging) as an adjunct to conventional techniques for imaging the cranio-cervical arteries(CTA, MRA, and DSA). Whilst adequate for revealing abnormalities of the vessel lumen, conventional techniques fail to fully characterize pathology that resides within the vessel wall. 1 Materials and Methods: We utilized VW-MR imaging in the pre-therapeutic work-up of two patients undergoing endovascular therapy: - A patient with a giant carotid ICA pseudoaneurysm - A patient with a complex vertebrobasilar junction fenestrated aneurysm with the aneurysm located asymmetrically in one limb of the fenestration. Results: VW-MR Imaging provided significant information that could not be discerned from conventional luminography: 1) Relatively acute thrombus may be differentiated from relatively chronic thrombus on the basis of layering, allowing for an assessment of the relative degree to which the patient may withstand aggressive endovascular manipulation. 2) Vessel wall contrast enhancement was depicted. While the exact significance of this finding is a subject of intense research 2, it has been suggested that this may reflect an underlying inflammatory etiology for the aneurysm. 3 3) The angio-architecture of both the aneurysm and the parent vessel were better depicted than on conventional imaging. 4) VW-MR imaging may provide reliable quantification of wall thickness. 4 5) VW-MR imaging was critical in defining the lumen with respect to the aneurysm sac in our fenestrated aneurysm case and in planning where to place a flow diverting stent. 5, 6 Conclusions: VW-MR Imaging has multiple potential benefits in the pre-therapeutic work-up of aneurysmal disease and is already used on a clinical basis at many centers. Figure Legends: : 1) VW-MR demonstrates position of the lumen for flow diverter placement. 2) Architecture of pseudoaneurysm is defined including outflow tract, high flow jet and extensive thrombus. Disclosures: G. Deib: None. B. Wasserman: None. M. Lim: None. G. Toth: None. E. Obusez: None.